2023
DOI: 10.3389/fcimb.2023.1077995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comprehensive genome analysis of novel bacteriophage, vB_Kpn_ZCKp20p, with lytic and anti-biofilm potential against clinical multidrug-resistant Klebsiella pneumoniae

Abstract: IntroductionThe rise of infections by antibiotic-resistant bacterial pathogens is alarming. Among these, Klebsiella pneumoniae is a leading cause of death by hospital-acquired infections, and its multidrug-resistant strains are flagged as a global threat to human health, which necessitates finding novel antibiotics or alternative therapies. One promising therapeutic alternative is the use of virulent bacteriophages, which specifically target bacteria and coevolve with them to overcome potential resistance. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 129 publications
1
5
0
Order By: Relevance
“…Given that the genomes of E. coli O177 phages were smaller than 200 kbp, they were classified as small phages. These findings were consistent with previous studies, which have reported small phages infecting other pathogenic bacteria such as E. coli, K. pneumoniae, P. aeruginosa, and Salmonella species [10][11][12][13][14]25 . Although TEM analysis revealed that E. coli O177 phages had similar morphotype 20 , BLASTn and PhageAI analysis classified these phages under the subfamilies Stephanstirmvirinae, Tevenvirinae, and Vequintavirinae within the Caudoviricetes class.…”
Section: Discussionsupporting
confidence: 93%
“…Given that the genomes of E. coli O177 phages were smaller than 200 kbp, they were classified as small phages. These findings were consistent with previous studies, which have reported small phages infecting other pathogenic bacteria such as E. coli, K. pneumoniae, P. aeruginosa, and Salmonella species [10][11][12][13][14]25 . Although TEM analysis revealed that E. coli O177 phages had similar morphotype 20 , BLASTn and PhageAI analysis classified these phages under the subfamilies Stephanstirmvirinae, Tevenvirinae, and Vequintavirinae within the Caudoviricetes class.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the control group, treatment with phage led to a distorted biofilm morphology and bacterium death. Phage vB_Kpn_ZCKp20p isolated from urban and medical sewage showed the ability to lyse biofilm-producing MDR K. pneumoniae isolates without cytotoxicity to human skin fibroblasts, and could inhibit biofilm formation and disrupt mature biofilms (Zaki et al, 2023). Polyvalent phage KL-2146 can infect NDM producing Klebsiella and antibiotic-sensitive K. pneumoniae 13, 883, which was demonstrated to effectively disrupt biofilms possessing multiple Klebsiella strains (Gilcrease et al, 2023).…”
Section: Phages In the Research Stagementioning
confidence: 99%
“…ARAGORN v1.2.41 was used to identify tRNA genes [45]. The presence of temperate genetic markers, bacterial virulence, and AMR genes was determined using PHageBACterioPHage LIfstyle Predictor (BACPHLIP v0.9.6) and PhageLeads to evaluate the phage's potential for therapeutic applications [46][47][48]. The circular genomic map was drawn using CGView on the PROKSEE server [49].…”
Section: Genome Analysis 2111 Assembly and Annotationmentioning
confidence: 99%
“…More phages filtered from the NCBI virus database (filtration criteria was Jerseyvirus and complete RefSeq genome) were analyzed using CoreGenes 5.0 to identify terminase genes conserved through the genus and family levels [55]. Terminase, a large subunit (TerL, signature gene), was used to construct a protein-based phylogenetic tree using the phylogeny.fr web-based tool [48,56]. The TerL tree was constructed to verify the assignment of phage ZCSE9 to the genus of the closely related matches according to intergenomic similarity analysis.…”
Section: Phylogenetic Analysismentioning
confidence: 99%